Pengembangan Alat Peraga Low Technology dan High Fidelity Dalam Praktik Pemasangan Alat Kontrasepsi dalam Rahim - Lindayani, I Komang; Suarniti, Ni Wayan; Dewi, I GAA Novya (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2023)
Practical simulations are important for midwifery vocational students to carry out before entering the real practice. The availability of adequate teaching aids will support the achievement of learning objectives. A practical demonstration tool for installing an intrauterine contraceptive device (IUD) was developed in this research using the principles of low technology and high fidelity. The aim of this research is to measure the practicality and effectiveness of the teaching aids developed. This study is research and development using the ADDIE (Assessment, Design, Development, Implementation and Evaluation) model. The research was conducted in July-September 2020 at the Denpasar Ministry of Health Polytechnic, Midwifery Department. The population of this study were Bachelor and Diploma of Midwifery students. The sample size was 30 respondent for each treatment and control group using proportional random sampling techniques. Practicality measurement uses a questionnaire, while effectiveness uses an observation sheet. The research results showed that the practicality score on the 5 aspects measured showed a score of > 3.40, which shows that this teaching aid is practical to use in practice. The Mann Whitney difference test was used to test the skill observation scores in the treatment and control groups, and obtained p-value = 0.240 (>0.05). This shows that the mean skill scores in the treatment and control groups are not significantly. The teaching aids developed are practical and effective for use in IUD installation practice. There is a need to develop other teaching aids to improve students' skills.